2019
DOI: 10.3389/fmicb.2019.02666
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Cultivable Microbiota in Fresh and Stored Mature Human Breast Milk

Abstract: Besides nutritional components, breast milk contains diverse microbes, which may be involved in colonization of the infant gut. Expressed milk is often stored for few days in the refrigerator. The aim of this study was to determine the abundance, prevalence and diversity of facultative and strict anaerobic bacteria using culture-dependent and -independent methods, and to determine changes in milk microbial and chemical composition during storage. Samples of mature breast milk from 21 women were collected 3–6 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 66 publications
1
17
0
Order By: Relevance
“…Introduction of new media, supplements and incubation conditions have allowed the isolation of bacteria that were previously unnoticed. However, recent developments in culturomics have revealed that many bacteria previously regarded as non-cultivable can now be isolated from complex ecosystems when a proper combination of culture conditions is provided (Lagier et al, 2012;Lagier et al, 2015;Lau et al, 2016;Lagier et al, 2018;Schwab et al, 2019). These new methodologies have served as critical tests to validate data derived from metagenomic studies regarding the gut ecosystem (Lau et al, 2016).…”
Section: The Composition Of the Human Milk Microbiotamentioning
confidence: 99%
“…Introduction of new media, supplements and incubation conditions have allowed the isolation of bacteria that were previously unnoticed. However, recent developments in culturomics have revealed that many bacteria previously regarded as non-cultivable can now be isolated from complex ecosystems when a proper combination of culture conditions is provided (Lagier et al, 2012;Lagier et al, 2015;Lau et al, 2016;Lagier et al, 2018;Schwab et al, 2019). These new methodologies have served as critical tests to validate data derived from metagenomic studies regarding the gut ecosystem (Lau et al, 2016).…”
Section: The Composition Of the Human Milk Microbiotamentioning
confidence: 99%
“…The most commonly reported genera in human milk include Staphylococcus, Streptococcus, Lactobacillus, Enterococcus, Bifidobacterium, Propionibacterium, as well as the family Enterobacteriaceae [36][37][38]. However, the types and amounts of bacteria in human milk are likely impacted by many factors including genetics, maternal health and diet, stage of lactation and geographic location [39].…”
Section: Microbiome and Probioticsmentioning
confidence: 99%
“…Of note, increasing observations demonstrate the presence of significant butyrate concentrations in breast milk, ranging from 0.01 to >5.0 mM ( 67 70 ) ( Table 2 ).…”
Section: The Potential Of Breastfeedingmentioning
confidence: 99%